Sharia Marketing and Halal Destination Branding: Is Building a Halal Destination Image Effective with Destination Branding Strategies? - Dhiya'u Shidiqy; Wedyan Fayez; Muhammad Isyak Putra Siregar (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2025)
East Java, a popular tourist destination in Indonesia, is committed to developing culinary tourism through the concept of a halal culinary area. This initiative also supports the acceleration of Micro, Small, and Medium Enterprise (MSME) product development. Furthermore, creating a positive perception and image of halal products through halal branding is crucial in supporting the halalization program for MSME products. Furthermore, ensuring that products are marketed according to Sharia principles is a key factor in building the halal industry. Of the various studies on product halalness, research on the image of halal products with halal branding that focuses on halal culinary areas has never been conducted. This study aims to determine the effect of halal branding on the image of halal destinations in the East Java Halal Culinary Area and its compliance with Sharia marketing principles. This study uses a quantitative method by examining the influence of independent variables on the dependent variable through a t-test using SPSS. The population in this study was buyers in the East Java Halal Culinary Area, and a sample of 110 people was selected using an accidental sampling technique. From a Sharia marketing perspective, the implemented branding strategy is in accordance with Sharia marketing principles. However, the results of this study indicate that the halal branding strategy in the East Java Halal Culinary Region does not influence the halal image or is unable to build the image of a halal destination in the region. The main finding is that while the branding strategy aligns with Sharia marketing principles, it does not significantly contribute to shaping the destination's halal image.